Suppression of inflammatory arthritis in human serum paraoxonase 1 transgenic mice - Christina Charles-Schoeman (Nature Portfolio, 2020)
Abstract Paraoxonase 1(PON1) is an HDL-associated protein, which metabolizes inflammatory, oxidized lipids associated with atherosclerotic plaque development. Because oxidized lipid mediators have also been implicated in the pathogenesis of rheumatoid arthritis (RA), we evaluated the role of PON1 in murine inflammatory arthritis. K/BxN serum transfer (STIA) or collagen antibody transfer (CAIA) was used for arthritis induction in B6 mice homozygous for the PON1 human transgene [PON1Tg], PON1 knock-out mice [PON1KO], and wild type littermate control mice [WT]. Experiments were also performed in K/BxN mice with chronic arthritis, and in RA patients and healthy controls. Arthritis activity in K/BxN mice was associated with a marked dyslipidemia, lower PON1 activity and higher bioactive lipid mediators (BLM), as well as a dysregulated hepatic lipid gene expression profile. Higher serum PON1 activity correlated with lower BLM and lower arthritis activity in both K/BxN mice and RA patients. Overexpression of the human PON1 transgene was associated with reduced inflammatory arthritis, which correlated strongly with higher circulating PON1 activity, upregulation of the hepatic glutathione pathway, and reduction of circulating BLM. These results implicate PON1 as a potential novel therapeutic target for joint disease in RA with potential for vascular benefit, which warrants further investigation.